The Effect of Water Sorption and Glass Transition Temperature on Non-Enzymatic Browning Reaction of Food Models - Dede R Adawiyab; S T Soekarto; P Hariyadi; Suyitno . (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
This research was aimer/ to study the extend of non enzymatic browning reaction in food models containing the mixture of tapioca starch, casein, sucrose and oh at different moisture contents (2.55%, 5.26%, 7.54%, 15.20%. 15.93% and 23.99%) and storage temperatures (30, 55 and 700C). The non-enzymatic browning reaction was detected from brown color intensity measured by spechtrophotometer and colorimetric methods. The non-enzymatic browning reaction or food model follow pseudo-zero order reaction, suggesting that browning reaction occurred at moisture content above monolayer zone. T-Tg (T storage - Tg prediction) and reaction rate constant (k) plots showed that browning reaction occurred at temperature around glass transition and increased significantly at 150 above Tg of casein. Tapioca starch in the food model was under glassy condition. The mobility of substrate increased and diffused at amorphous matrix. Keywords : glass transition, non-enzymatic browning, glassy, amorphous